ANALISIS KEPUASAN SEKOLAH MITRA TERHADAP MAHASISWA PRAKTEK LAPANGAN KEPENDIDIKAN FKIP UMMY TAHUN 2022 - Hana Adhia; Helvita Roza; Risza Dwi Putri; Roza Zaimil; Redo Andi Marta; Ikhwan (LPPM Universitas Ekasakti, 2024)
This research analyzes the level of satisfaction of Mitra schools towards educational field practice students using a qualitative descriptive research method with a percentage formula. The focus of the research is the results of the analysis carried out at the training school for PLK students for the Odd Semester 2022/2023, Faculty of Teacher Training and Education, Mahaputra Muhammad Yamin University. This research framework relies on the foundation of thoughts, ideas and policies in the 2022 PLK guidebook. There are 22 training schools for PLK, consisting of 10 middle schools and 12 high schools in public and private schools in Solok City and Regency. Comprehensive analysis of the data shows that the results of the Training School Satisfaction Survey for Educational Field Practice students can be concluded that the results of training school satisfaction with PLK on student Ethics were found to be in the highest percentage of very satisfied (88%), communication was obtained in a satisfied percentage (81%), the ability to use technology is also very satisfied (88%), self-development presentation is satisfied (83%) in the sense that PLK FKIP UMMY students are liked by many respondents and they feel very satisfied. This research explains in detail the essence of implementing PLK which can provide advantages and benefits for schools and tutors and provide an in-depth understanding of their roles.